The Influence of Current Ratio, Debt to Equity Ratio, Inventory Turnover, Return on Assets and Firm Size Toward Profit Growth of Consumer Goods Company Listed on Indonesia Stock Exchange - Clarissa Caitlin; Yanuar Dananjaya (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This research is conducted to analyze the influence of Current Ratio, Debt to Equity Ratio, Inventory Turnover, Return on Assets and Firm Size toward Profit Growth of Consumer Goods Companies listed in the Indonesia Stock Exchange for the period 2018 – 2022. The quantitative approach will be used in this study's research design. The research quantitative data is the secondary data acquired from the financial year reports of Consumer Goods Companies listed on the Indonesia Stock Exchange from 2018 to 2022. With purposive sampling technique, 30 companies out of 84 companies in the population are chosen as the sample for this research. SPSS Version 25 is used to compute the multiple linear regression model of this research. The research’s result shows that Current Ratio partially has insignificant influence towards Net Profit Margin. Receivable Turnover partially has insignificant influence towards Profit Growth. Debt to Equity Ratio partially has insignificant influence towards Profit Growth. Return on Assets partially has significant influence towards Profit Growth. Inventory Turnover partially has insignificant influence towards Profit Growth. Firm Size partially has insignificant influence towards Profit Growth. Current Ratio, Debt to Equity Ratio, Return on Assets, Inventory Turnover and Firm Size simultaneously have insignificant influence towards Profit Growth.